Brainstem metastases treated with Gamma Knife stereotactic radiosurgery: the Indiana University Health experience. (January 2018) - Patel, Ajay; Mohammadi, Homan; Dong, Tuo; Shiue, Kevin Ren-Yeh; Frye, Douglas; Le, Yi; Ansari, Shaheryar; Watson, Gordon A; Miller, James C; Lautenschlaeger, Tim
Brainstem metastases offer a unique challenge in cancer treatment, yet stereotactic radiosurgery (SRS) has proven to be an effective modality in treating these tumors. This report discusses the clinical outcomes of patients with brainstem metastases treated at Indiana University with Gamma Knife (GK) radiosurgery from 2008 to 2016. 19 brainstem metastases from 14 patients who had follow-up brain imaging were identified. Median tumor volume was 0.04 cc (range: 0.01–2.0 cc). Median prescribed dose was 17.5 Gy to the 50% isodose line (range: 14–22 Gy). Median survival after GK SRS treatment to brainstem lesion was 17.2 months (range: 2.8–45.6 months). The experience at Indiana University confirms the safety and efficacy of range of GK SRS prescription doses (14–22 Gy) to brainstem metastases.